Does Government Expenditure in Education Cause Economic Growth: ASEAN-5 Perspective - Taasim, S. (International Journal of Human and Technology Interaction (IJHaTI), 2020)
Debates on linkages between education expenditure and economic growth have gained attention from economists, especially based on Wagner Law. Education expenditure is listed as a government public expenditure with the highest accumulation in yearly budget for ASEAN-5, which includes Malaysia, Indonesia, the Philippines, Singapore and Thailand. This empirical study aimed to examine the relation between education expenditure and economic growth in ASEAN-5 over the 2000-2018 periods. To achieve the objective, it was more appropriate to examine the estimation model was. With regard to the fixed effects model, there was no relation between education expenditure and economic growth. Furthermore, the analysis has proved that labour force and capital accumulation were important variables which influence economic growth.